Interannual variation and chemical characterization of major water-soluble inorganic ions in snow across Northwest China - Zhang, Yuxuan; Wang, Ninglian; Zhang, Bo; Zhang, Wei; Shen, Baoshou (Frontiers in Earth Science, 2023)
From November 2018 to April 2020, 426 snow samples were collected near two field observation sites in Heihe and Altay, Northwest China, and the pH and major water-soluble inorganic ions (Ca2+, SO42－, Na+, NO3－, Cl－, K+, Mg2+ and NH4+) were analyzed. To identify the source of ions, enrichment factor method, Pearson correlation analysis, and HYSPLIT (Hybrid Single Practical Lagrangian Integrated Trajectory) backward trajectory analysis were employed. Snow was nearly neutral and the Ca2+ was the dominate cation in snow. The anion concentration demonstrate high variability. Affected by geographical location and atmospheric circulation, the concentration of soluble inorganic ions in snow from Altay region was higher than that Heihe region and remote areas with high altitude or high latitude. Compared with 2018/2019, the ions in snow increased in 2019/2020, especially in Altay region. Moreover, the temporally trend of ion concentrations was stable, indicating that the source and migration path of ion concentration had strong consistency. Our study suggested that terrestrial sources are the main driven factors for the ions observed in snow samples from Northwest China, and some ions are also influenced by anthropogenic sources (NH4+, SO42－ and NO3－), marine sources (Cl－ and Na+) and salt mine dust (Cl－, Na+, SO42－ and K+).